Early-stage hip involvement in patients with ankylosing spondylitis: A Chinese study based on magnetic resonance imaging. Issue 6 (1st November 2016) - Chen, Dongying; Yuan, Shiwen; Zhan, Zhongping; Xiao, Youjun; Li, Hao; Liang, Liuqin; Yang, Xiuyan
Abstract: Objectives : To evaluate the clinical characteristics and identify potential factors of the early-stage hip involvement in patients with ankylosing spondylitis (AS) based on the magnetic resonance imaging (MRI). Methods : A cross-sectional retrospective study of 655 consecutive patients was performed. Patients with hip pain or limited hip function but lacking definitive evidence of hip involvement on radiography underwent hip MRI. Based on the results of the imaging tests, the patients were classified into three categories: (1) no hip involvement; (2) early-stage hip involvement according to MRI but not radiography; (3) advanced-stage hip involvement according to a Bath Ankylosing Spondylitis Radiology Index-hip score ≥2. Results : One hundred and sixty-eight patients had early-stage hip involvement and 103 patients had advanced-stage hip involvement. Multivariate logistic regression analysis indicated that younger age at onset, worse BASMI score, and more active inflammation in the sacroiliac joints were associated with the occurrence of early-stage hip involvement. Conclusion : Negative plain radiography results cannot be used to rule out hip involvement. MRI was superior to radiography for the detection of early-stage hip involvement. Susceptible AS patients with symptoms or risk factors for hip involvement should undergo hip MRI to test for lesions in the early stage.